The Effects of Norms on Environmental Behavior - Dannenberg, Astrid; Gutsche, Gunnar; Batzke, Marlene C. L.; Christens, Sven; Engler, Daniel; Mankat, Fabian; Möller, Sophia; Weingärtner, Eva; Ernst, Andreas; Lumkowsky, Marcel; von Wangenheim, Georg; Hornung, Gerrit; et al. (Review of Environmental Economics and Policy)

Social norms and individual climate protection activities: A survey experiment for Germany - Engler, Daniel; Gutsche, Gunnar; Simixhiu, Amantia; Ziegler, Andreas (Energy Economics)

Determinants of individual sustainable investment behavior - A framed field experiment - Gutsche, Gunnar; Wetzel, Heike; Ziegler, Andreas (Journal of Economic Behavior & Organization)

On the relationship between corporate CO2 offsetting and pro-environmental activities in small- and medium-sized firms in Germany - Engler, Daniel; Gutsche, Gunnar; Simixhiu, Amantia; Ziegler, Andreas (Energy Economics)

Acceptance of climate-oriented policy measures under the COVID-19 crisis: an empirical analysis for Germany - Engler, Daniel; Groh, Elke D.; Gutsche, Gunnar; Ziegler, Andreas (Climate Policy)

Who wants to get involved? Determining citizen willingness to participate in German renewable energy cooperatives - Fischer, Beate; Gutsche, Gunnar; Wetzel, Heike (Energy Research & Social Science)

Revisiting the determinants of individual sustainable investment—The case of Japan - Gutsche, Gunnar; Nakai, Miwa; Arimura, Toshi H. (Journal of Behavioral and Experimental Finance)

Investment Barriers and Labeling Schemes for Socially Responsible Investments - Gutsche, Gunnar; Zwergel, Bernhard (Schmalenbach Business Review)
Abstract Given the increasing role of socially responsible investing (SRI), but still limited participation of individual (i.e. small, retail) investors, the objective of this study is twofold: (i) We aim to identify investment barriers regarding SRI for individual investors and analyze to what extent these barriers vary across different investor groups. (ii) We analyze to what extent sustainability or transparency labels can help to overcome these barriers. To this end, we empirically analyze data from a survey and a stated choice experiment for a broad sample of financial decision makers in German households. The results suggest that a considerable amount of respondents can imagine to invest in a socially responsible manner, which is promising for policymakers and practitioners who aim to foster sustainable development and SRI. However, too high information costs are a severe barrier for potential future investors and a considerable share of respondents distrusts providers of socially responsible investment products. Banks, who could help to solve this problem, appear not to fulfill their role as intermediaries. But we find that labels might serve as a complement to banks. Especially sustainability certificates that confirm the consideration of sustainability criteria could decrease information costs and overcome at least some barriers for some investor groups, particularly for new investors. However, the results also suggest that a certain degree of basic knowledge and trust in providers of socially responsible investment products is required before labels work efficiently.

Which private investors are willing to pay for sustainable investments? Empirical evidence from stated choice experiments - Gutsche, Gunnar; Ziegler, Andreas (Journal of Banking & Finance)

On the relevance of contextual factors for socially responsible investments: an econometric analysis - Gutsche, Gunnar; Köbrich León, Anja; Ziegler, Andreas (Oxford Economic Papers)